CTD data for Elephant Butte Reservoir near the mouth of the Rio Grande (March and May 2022) - Abigail Eckland; Irina Overeem; Brandee Carlson (PANGAEA, 2023)
Conductivity, Temperature, and Depth (CTD) data was collected within and near the mouth of the Rio Grande in March and May 2022 to measure potential water column stratification. CTD data was collected with a SonTek CastAway CTD from a packraft.
In: Eckland, A et al. (2023): Sediment, hydrologic, and temperature data collected from the Rio Grande Delta upstream of Elephant Butte Reservoir, NM (July 2021-September 2022) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.961886